Maths challenge - Gardiner, Tony (Oxford University Press, 2000)
Maths Challenge has been written to provide an enrichment programme for able students at lower secondary level. * Challenges provide stimulating questions to help students think more deeply about basic mathematical ideas * Comments and solutions explain the mathematical ideas and provide tips on how to approach later questions * A Glossary defines all the mathematical terms used in the books in a precise way, making the books self-contained * Suitable for individual, group, or class work, in school, or at home